Proposal for an individualized dietary strategy in patients with very long‐chain acyl‐CoA dehydrogenase deficiency. Issue 1 (11th February 2019) - Bleeker, Jeannette C.; Kok, Irene L.; Ferdinandusse, Sacha; de Vries, Maaike; Derks, Terry G.J.; Mulder, Margot F.; Williams, Monique; Gozalbo, Estela Rubio; Bosch, Annet M.; van den Hurk, Dorine T.; de Sain‐van der Velden, Monique G.M.; Waterham, Hans R.; et al.
Abstract: Background: Patients with very long chain acyl‐CoA dehydrogenase deficiency (VLCADD), a long chain fatty acid oxidation disorder, are traditionally treated with a long chain triglyceride (LCT) restricted and medium chain triglyceride (MCT) supplemented diet. Introduction of VLCADD in newborn screening (NBS) programs has led to the identification of asymptomatic newborns with VLCADD, who may have a more attenuated phenotype and may not need dietary adjustments. Objective: To define dietary strategies for individuals with VLCADD based on the predicted phenotype. Method: We evaluated long‐term dietary histories of a cohort of individuals diagnosed with VLCADD identified before the introduction of VLCADD in NBS and their beta‐oxidation (LC‐FAO) flux score (rate of oleate oxidation) in cultured skin fibroblasts in relation to the clinical outcome. Based on these results a dietary strategy is proposed. Results: Sixteen individuals with VLCADD were included. One had an LC‐FAO flux score >90%, was not on a restricted diet and is asymptomatic to date. Four patients had an LC‐FAO flux score <10%, and significant VLCADD related symptoms despite the use of strict diets including LCT restriction, MCT supplementation and nocturnal gastric drip feeding. Patients with an LC‐FAO flux score between 10 and 90% ( n = 11) showed a more heterogeneous phenotype. Conclusions: This study shows that a strict diet cannot prevent poor clinical outcome in severely affected patients and that the LC‐FAO flux is a good predictor of clinical outcome in individuals with VLCADD identified before its introduction in NBS. Hereby, we propose an individualized dietary strategy based on the LC‐FAO flux score.